INTERFAITH DIALOGUE IN ISLAMIC RELIGIOUS EDUCATION: A THEOLOGICAL AND PEDAGOGICAL FRAMEWORK - Rifka Kurnia; Syaiful Hadi (FAJAR Jurnal Pendidikan Islam, 2026)
The reality of religious diversity in modern society requires Islamic Religious Education (PAI) to develop learning models that foster inclusive, dialogical, and constructive religious understanding. This study aims to analyze the theological and pedagogical foundations of interfaith dialogue in PAI and to formulate a conceptual framework applicable to contemporary educational contexts. This research employs a library-based approach by reviewing primary and secondary literature related to Islamic theology, dialogical pedagogy, and discourses on religious plurality. The findings reveal that interfaith dialogue has strong legitimacy within Islamic teachings through the principles of ta‘āruf, justice, public good, and the recognition of diversity as part of divine design. Pedagogically, interfaith dialogue enhances critical thinking, empathy, cross-religious communication, and students’ resilience toward unfiltered religious information in the post-truth era. Moreover, teachers hold a central role as facilitators of dialogue, ethical role models, and guarantors of psychological safety in classrooms that respect differences. This study emphasizes the urgency of integrating interfaith dialogue into PAI curricula, teaching methods, and learning activities to shape Muslim learners who are peaceful, rational, and capable of living harmoniously in plural societies. These findings offer a conceptual contribution for developing a more humanistic and globally relevant PAI curriculum.